Kelong dalam perspektif Hermeneutika - Ali, Muhammad (citeus, 2010)
This qualitataive study aims to describe and explain a) the structure of ke- long, b) the function of kelong, and c) the value of kelong. The research was carried out using the following procedure: transcribing kelong texts, interpreting the kelong texts, and referencing the results of text analysis to articles related to the culture and literature of Makassar. Some in-depth interviews with key people about the culture were also conducted. It was found that kelong consists of micro, macro, and super structures. In the case of functions, it was found that the functions consist of infor- mational, emotive, directive, poetic, and esthetic functions. In the case of values, ke- long covers religious, philosophic, and ethic, and esthetic of siri na pacce.